Long-Run Elasticity of the Substitution in the Slovak Economy (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2017)
The value of the Slovak long-run elasticity substitution is relatively slow – about 0.10. It follows from the estimate of low-frequency econometric model. Econometric form is given by the capital demand derived from the first-order conditions of the firm maximizing its profit. Due to the robustness we use different measures of the economic variables. The basic data gathered from the National Bank of Slovakia data portal consists of the real and nominal output, nominal capital, output price and different interest rates. A challenge is to find real capital time series. One way is to use a net investment deflator computed from the real and nominal gross fixed investment and the consumption of the fixed capital. The low-pass filter of data series is used to measure the long-run value of variables.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.